Investigative production about family matters from 1994 to 2010 in the west central metropolitan area: reflexive analysis about the state of the art (2020)
This theoretical article tries to make a reflexive analysis about the state of the art on the investigative production about the family topic; this process will be analyzed from 1994 to 2010 in the West Central Metropolitan area, with the aim to identify the topics discussed by the authors in this area of knowledge, central concerns, conceptual tendencies and methodologies implemented at the time of investigating the family as an object of study. This work allowed knowing the transformations and changes in family dynamics; it was emphasized in the present situation of Colombian families aiming to identify the population and the issues less addressed by the authors. It is expected to be retaken, in future processes, investigative routes that would evidence the possible problems and needs of families at that moment.